The Effect of Average School Age, Per Capita GDP and Unemployment on Absolute Poverty in Meranti Island Regency - Ricky Seven Octo Waruwu; I. Isyandi; Eka Armas Pailis (Manunggal Halim Jaya, 2026)
This study aims to analyze the effect of average years of schooling, per capita GRDP, and unemployment on absolute poverty in the Meranti Regency Islands, both simultaneously and partially. The study is motivated by the relatively high poverty rate and fluctuating socio-economic conditions in the region. This research employs a quantitative approach using multiple linear regression analysis with the assistance of EViews software. The data used are secondary time series data from 2010–2024 obtained from the Central Statistics Agency (BPS). The analysis includes classical assumption tests (normality, multicollinearity, autocorrelation, and heteroscedasticity) and statistical tests such as t-test, F-test, and coefficient of determination (R²). The results indicate that, simultaneously, average years of schooling, per capita GRDP, and unemployment have a significant effect on absolute poverty in the Meranti Regency Islands. Partially, average years of schooling and per capita GRDP have a negative and significant effect on poverty, implying that improvements in education and income levels can reduce poverty. Meanwhile, unemployment has a positive and significant effect on poverty, indicating that higher unemployment increases poverty levels. These variables collectively explain a substantial proportion of the variation in poverty within the model.